ANALISIS SEMIOTIK MANTRA PENGOBATAN PADA MASYARAKAT DAYAK BAKUMPAI DI KABUPATEN BARITO SELATAN KALIMANTAN TENGAH - Resviya, Resviya (Meretas: Jurnal Ilmu Pendidikan, 2019)
This study aims to explain the function of the mantra of medicine in the Bakumpai Dayak Society in South Barito District and the relevance of Mantra as local wisdom in relation to Islam. This research uses a descriptive qualitative approach using research locations in Gunung Bintang Awai Subdistrict, Dusun Hilir Subdistrict, North Dusun Subdistrict and South Dusun Subdistrict, South Barito Regency, Central Kalimantan. The method used in this research is descriptive method, with a qualitative form of research, and uses the Charles Sanders Peirce semiotic approach. The data source of this research is the results of interviews with spell speakers, observational data, and the results of recording in the field. The results of this study have shown that the meanings contained in the mantra of treatment in the Bakumpai Dayak Society in the South Barito Regency analyzed are 3, namely: religious meaning, social meaning, and personality meaning. First, the religious meaning: belief in God Almighty, belief in angels, belief in the Qur'an, belief in the apostles, pray to God, weak human beings, and demons to human enemies. Second, the meaning of society: mutual cooperation. Third, the meaning of personality: the wisdom contained in the mantra of treatment in the Dayak Bakumpai Society in South Barito Regency that is analyzed, namely: as a projection. Functions that validate culture, as an educational tool, and as a means of enforcing the values / norms of society. Mantra structures are covered with mystical, magical, mythological, sound, diction, and imagination formulas. Discourse on the value of Islam has been very dominant in the language of Mantra. The Arabic Substance is also embedded in the text of the Mantra and results in new special characteristics. This condition has made certain characters from the Mantra text. such as the synthesis between the Bakumpai language and Islamic culture in one combination and from another tradition, the Bakumpai Dayak culture. Based on this research, it can be concluded that the Mantra belonging to the Dayak Bakumpai tribe can be interpreted freely as a method or concept expressed in words and it confirms that the Mantra has an invisible power and has also been made as a penetration of solving the problems of life in society.